HIV Infection and TLR Signalling in the Liver. (22nd February 2012) - Crane, Megan; Visvanathan, Kumar; Lewin, Sharon R.
Abstract : Despite the availability of effective combination antiretroviral therapy (cART), liver disease is one of the leading causes of morbidity and mortality in Human Immunodeficiency Virus (HIV)-infected individuals, specifically, in the presence of viral hepatitis coinfection. HIV, a single stranded RNA virus, can bind to and activate both Toll-like receptor (TLR)7 and TLR8 in circulating blood mononuclear cells, but little is known about the effect of HIV on TLRs expressed in the liver. HIV can directly infect cells of the liver and HIV-mediated depletion of CD4+ T-cells in the gastrointestinal tract (GI tract) results in increased circulating lipopolysaccharide (LPS), both of which may impact on TLR signaling in the liver and subsequent liver disease progression. The potential direct and indirect effects of HIV on TLR signaling in the liver will be explored in this paper.